Kavik the wolf dog - Annakin, Ken.; Heston, Charlton; Mercier, Michele; Eastman, George; Cox, Ronny; Sorengen, Linda; McMillan, Andrew Ian.; Ireland, John, 1914-1992; GoodTimes Home Video (Firm) (New York : GoodTimes Home Video, 2002)
A magnificent Alaskan dog who leads his team to victory in the National Open Sled Dog Race, Kavik is bought by wealthy, unscrupulous businessman George Hunter, but his plane crashes en route to Seattle. Twelve-year-old Andy finds the badly wounded Kavik in the woods, nurses him back to health when no one believes he will survive, and loves the once proud dog, who is left fearful and cowardly by the accident. Hearing of Kavik's amazing recovery, Hunter takes the dog back to Seattle to show him off, but when Kavik becomes frightened at Hunter's annual Sportsman's Dinner, he leaps through a glass window to freedom. Lost and alone, he must regain his courage, battling man and the elements on his 2,000-mile trek to find the boy he loves.
Ronnie Cox, Linda Sorengen, Andrew Ian McMillan, Chris Wiggins, John Ireland.
DVD, mono, Dolby digital.
Keywords: Feature films; Dogs; Klondike River Valley (Yukon) -- Gold discoveries